Inclusive diets within planetary boundaries - Kawarazuka, Nozomi; Mabhaudhi, Tafadzwanashe; Green, R.; Scheelbeek, P.; Ambikapathi, R.; Robinson, J.; Mangnus, E.; Béné, Christophe; Cavatassi, R.; Kalita, U.; Gelcich, Stefan; Cheserek, M.; et al. (Elsevier, 2023)
Our food production system is unsustainable and threatening planetary boundaries. Yet, a quarter of the global population still lacks access to safe and nutritious food, while suboptimal diets account for 11 million adult deaths per year. This Voices asks: what critical barriers must be overcome to enable sustainable, healthy, accessible, and equitable diets for all?